The effect of increasing temperature on crop photosynthesis: from enzymes to ecosystems. (23rd February 2021) - Moore, Caitlin E; Meacham-Hensold, Katherine; Lemonnier, Pauline; Slattery, Rebecca A; Benjamin, Claire; Bernacchi, Carl J; Lawson, Tracy; Cavanagh, Amanda P
Abstract : This review explores current understanding in crop photosynthesis and temperature across scales, linking enzyme processes within the leaf to stomata, plant transport systems, individual plants, and ecosystem-scale responses. Abstract: As global land surface temperature continues to rise and heatwave events increase in frequency, duration, and/or intensity, our key food and fuel cropping systems will likely face increased heat-related stress. A large volume of literature exists on exploring measured and modelled impacts of rising temperature on crop photosynthesis, from enzymatic responses within the leaf up to larger ecosystem-scale responses that reflect seasonal and interannual crop responses to heat. This review discusses (i) how crop photosynthesis changes with temperature at the enzymatic scale within the leaf; (ii) how stomata and plant transport systems are affected by temperature; (iii) what features make a plant susceptible or tolerant to elevated temperature and heat stress; and (iv) how these temperature and heat effects compound at the ecosystem scale to affect crop yields. Throughout the review, we identify current advancements and future research trajectories that are needed to make our cropping systems more resilient to rising temperature and heat stress, which are both projected to occur due to current global fossil fuel emissions.